2018
DOI: 10.1002/anie.201801842
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dispersion on the Structure of Diphenyl Ether Aggregates

Abstract: Dispersion interactions can play an important role in understanding unusual binding behaviors. This is illustrated by a systematic study of the structural preferences of diphenyl ether (DPE)-alcohol aggregates, for which OH⋅⋅⋅O-bound or OH⋅⋅⋅π-bound isomers can be formed. The investigation was performed through a multi-spectroscopic approach including IR/UV and microwave methods, combined with a detailed theoretical analysis. The resulting solvent-size-dependent trend for the structural preference turns out to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 17 publications
1
23
1
Order By: Relevance
“…Upon comparison to the series of diphenyl ether-solvent complexes 37 and also the phenyl vinyl ether-methanol complex, 38 the absence of backbone deformation in the DBF complexes proves to be true, as no structures were found involving a nonplanar DBF structure, which is not surprising since aromaticity is preserved. The influence of CHÁ Á ÁO contacts -playing a decisive role in DPE and PVE complexes -partly remains in the DBF-solvent structures as well.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Upon comparison to the series of diphenyl ether-solvent complexes 37 and also the phenyl vinyl ether-methanol complex, 38 the absence of backbone deformation in the DBF complexes proves to be true, as no structures were found involving a nonplanar DBF structure, which is not surprising since aromaticity is preserved. The influence of CHÁ Á ÁO contacts -playing a decisive role in DPE and PVE complexes -partly remains in the DBF-solvent structures as well.…”
Section: Discussionmentioning
confidence: 93%
“…In previous studies, we established a multi-spectroscopic approach in order to elucidate the preferred binding sites in different aromatic ether-alcohol and -water complexes. [34][35][36][37][38] Within the series of diphenyl ether (DPE) complexes, we have shown that water and small alcohol molecules prefer the p-docking site, whereas larger alcohols preferably bind to the ether oxygen atom. This observation contradicts the intuitive expectation of a preferred p docking, when the size of the alcohol increases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[40] In other studies exploring the interactions of water and alcohols with ethers, changes in the preferred primary bonding, OÀH•••O versus OÀH•••p,w ere observed due to dispersion effects ands tructural flexibility. [41,42] The data presented here provideu seful experimental benchmarks forc omputationalm ethods, in particular for analysing and accurately describing the effects of dispersion and competing interactions. In this respect, B3LYP-D3BJ is emerginga s ar eliable cost-efficient method, whereas MP2 and M06-2X exhibit deficiencies that impact on their predictions of the structures and energetics of molecular systemsw ith severalw eak hydrogen bonds and dispersive interactions.…”
Section: Discussionmentioning
confidence: 99%
“…24 The competition between these two sites of diphenylether-methanol complexes can essentially be tipped to either side by chemical substitution on the ether or the alcohol. 22,25,26 Aromatic ring methylation has been used before to tip the balance in anisole microsolvation experiments. 26 While we have included the case of water and ethanol solvation, the main focus of this work is on methanol and tert-butyl alcohol, which differ significantly in their secondary dispersion interaction.…”
Section: Introductionmentioning
confidence: 99%